Scoping Review: Diarrhea in Toddlers and Causing Factors - Endang Susilowati; Yuli Astuti; Refi Mulyasih (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Diarrhea is a disease caused by infection with microorganisms including bacteria, viruses, parasites, and protozoa, and its transmission is fecal-oral. Diarrhea is a condition where stool is excreted abnormally or not as usual, characterized by an increase in volume, dilution, and frequency of bowel movements more than 3 times a day and in neonates more than 4 times a day with or without blood mucus. Diarrheal disease is still a public health problem in developing countries such as Indonesia, with high morbidity and mortality. From the IDHS results, it was found that 13.7% of children under five experienced diarrhea in the two weeks before the survey, 3% higher than the IDHS findings. The highest prevalence of diarrhea is in children aged 12-23 months, followed by those aged 6-11 months and those aged 23-45 months. (Ministry of Health, 2011). Research objective: This study aims to analyze the factors that influence the incidence of diarrhea in toddlers, based on the results of previous studies. Method: This research was conducted using the scoping review method using several data-based electronic media: Pubmed, DOAJ, Scopus, Sinta, and limited database, namely the last 10 years starting 2012-2021. There were 20 articles used which discussed the causes of diarrhea in toddlers. Results: Factors causing diarrhea that were intensified include the mother's knowledge about hygiene and environmental hygiene, unsanitary water sources, latrines in the family, and health services that are difficult to reach, giving complementary foods too early, and germ infection factors, toddler nutrition factors low and mother's knowledge of diarrhea in toddlers, posyandu visits, non-exclusive breastfeeding and use of milk bottles and hygiene, number of family members and low economic status.